PERAN STAKEHOLDERS DALAM IMPLEMENTASI KEBIJAKAN INTERVENSI GIZI SENSITIF DI KOTA SEMARANG - Isro Lailia; Kismartini Kismartini; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2021)
The sensitive nutrition intervention policy is one of the policies of the Indonesian government as an effort to overcome the stunting problem, the implementation of which involves various parties. The policy is considered capable of overcoming the stunting problem by 70%. In Semarang City, even though this policy has been implemented, the stunting rate in Semarang City still shows an increase. So there is still a question about the role of stakeholders in the implementation of sensitive nutrition intervention policy in the Semarang City. The purpose of this research is to identify stakeholders in implementing sensitive nutrition intervention policy in Semarang City and analyzing its role. This research uses qualitative research methods with data collection techniques through interview and literature study. The theory used in this research is role of stakeholders by Nugoroho. The results showed that the stakeholders in implementing sensitive nutrition intervention policy in Semarang City were the Health Office, Fisheries Service, Education Service, Food Security Service, Population Control and Family Planning Service, DP3A, Bappeda, Puskesmas, Posyandu, IDI, physiotherapist, psychologist, community and private. StakeholdersThese roles are divided into five, namely policy creator, implementor, coordinator, facilitator, and accelerator. The recommendations given are coordination among stakeholders is to be increased, formulate regulations specifically discussing stunting, stakeholders must considered the program objective.